WAYS TO EXPAND THE TAX ADMINISTRATION BASE IN UZBEKISTAN BY INTRODUCING MODERN TECHNOLOGIES INTO TAX ADMINISTRATION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In order to further improve the tax system in our republic, reduce hidden circulation in the economy and implement the main directions of the concept of improving the fair tax policy of the Republic of Uzbekistan, the President of the Republic of Uzbekistan on July 10, 2019 "Additional measures to improve the tax administration" In order to further improve the activities of the Tax Service bodies, tasks such as automation of the Tax Administration process have been defined in the Decision No. PQ-4389.